Porcine von Willebrand Factor Binding to Human Platelet GPIb Induces Transmembrane Calcium Influx - Mazzucato, Mario; De Marco, Luigi; Pradella, Paola; Masotti, Adriana; Pareti, Francesco I (Thrombosis and Haemostasis, 1996)
Porcine von Willebrand factor (P-vWF) binds to human platelet glycoprotein (GP) lb and, upon stirring (1500 rpm/min) at 37° C, induces, in a dose-dependent manner, a transmembrane flux of Ca2+ ions and platelet aggregation with an increase in their intracellular concentration. The inhibition of P-vWF binding to GP lb, obtained with anti GP lb monoclonal antibody (LJ-Ib1), inhibits the increase of intracellular Ca2+ concentration ([Ca2+]i) and platelet aggregation. This effect is not observed with LJ-Ib10, an anti GP lb monoclonal antibody which does not inhibit the vWF binding to GP lb. An anti GP Ilb-IIIa monoclonal antibody (LJ-CP8) shown to inhibit the binding of both vWF and fibrinogen to the GP IIb-IIIa complex, had only a slight effect on the [Ca2+]i rise elicited by the addition of P-vWF. No inhibition was also observed with a different anti GP IIb-IIIa monoclonal antibody (LJ-P5), shown to block the binding of vWF and not that of fibrinogen to the GP IIb-IIIa complex. PGE1, apyrase and indomethacin show a minimal effect on [Ca2+]i rise, while EGTA completely blocks it. The GP lb occupancy by recombinant vWF fragment rvWF445-733 completely inhibits the increase of [Ca2+]i and large aggregates formation. Our results suggest that, in analogy to what is seen with human vWF under high shear stress, the binding of P-vWF to platelet GP lb, at low shear stress and through the formation of aggregates of an appropriate size, induces a transmembrane flux of Ca2+, independently from platelet cyclooxy-genase metabolism, perhaps through a receptor dependent calcium channel. The increase in [Ca2+]i may act as an intracellular message and cause the activation of the GP IIb-IIIa complex.